Functional composition of temperate forest trees under chronic ungulate herbivory. (10th April 2018) - Hedwall, Per‐Ola; Churski, Marcin; Jędrzejewska, Bogumiła; Miścicki, Stanisław; Kuijper, Dries Pieter Jan
Abstract: Question: Functional plant traits often express consistent changes along ecological gradients and, hence, are often used as indicators of environmental change (e.g. nutrient availability, temperature changes). Besides being driven by edaphic conditions, functional plant composition is filtered by herbivory, and traits responsive to nutrient availability often coincide with those related to palatability or resistance to browsing. We hypothesized that herbivory may distort the ways in which traits are expressed along environmental gradients. Location: Białowieża National Park, Poland. Methods: We used a long‐term controlled, exclosure experiment in the Białowieża National Park to study tree functional trait expression and plant indicator values, with and without large ungulate browsing, along a natural soil fertility gradient. Results: Browsing largely reduced the functional diversity of regenerating trees, indicated by multivariate analysis and Rao's Quadratic Entropy (RQE), and altered how several traits change with increasing fertility. Browsing led to an increase in specific leaf area (SLA) on poorer sites. RQE showed a hump‐backed trend along the fertility gradient, indicating the largest functional diversity at intermediate fertility. However, this pattern was not affected by browsing. Unlike the morphological tree traits, trends of light and N plant indicator values along the gradient were unaffected by browsing. Conclusions: These results highlight how the expression of plant traits resulting from one driver (soil fertility) can be modified by another driver (herbivory, ) and stress the importance of taking herbivory into account when using plant traits as indicators of large‐scale processes (e.g. climate change). Furthermore, the results suggest that plant indicator values may be more robust towards these effects, while compiled indices such as RQE could mask considerable functional turnover. Several traits (e.g. SLA) are strongly connected to nutrient cycling. The development, driven by browsing, towards higher SLA on poorer sites may thus cause a positive feedback effect on site fertility that drives an increase in nutrient availability. This may in turn have implications for ecosystem functionality. Hence, the large reduction in functional diversity revealed at the scale of this study may in the long term have implications on multiple ecosystem processes. Abstract : We used an exclosure experiment in the Białowieża National Park to study the effects of herbivory on the expression of plant traits resulting from soil fertility. Browsing by large ungulates altered how traits (especially specific leaf area) changed along a fertility gradient which stresses the importance of taking herbivory into account when using traits as indicators of large scale processes.